PENGARUH ORANG (PEOPLE), BUKTI FISIK (PHYSICAL EVIDENCE) DAN PELAYANAN (PROCESS) TERHADAP KEPUTUSAN PASIEN UNTUK MELAHIRKAN DI RUANG BERSALIN RUMAH SAKIT RAJAWALI CITRA - Susanti, Wahyu Febri Eka; Murtini, Mukti (PRIMA EKONOMIKA, 2024)
ABSTRACT This study means to decide the impact of people, physical evidence,and process on patient decisions. The sample of this study used 100respondents who came from patients who had given birth in the deliveryroom at Rajawali Citra Hospital. This type of quantitative research usesobservation methods and field surveys by determining several variable from the object under study and then making measurement instruments. The data analysis method used was tested using SPSS software version20.0. The results of the research on partial hypothesis testing stated: (1)The person variable partially did not significantly influence patient decisionsby 7.8%. (2) The physical evidence variable partially does not significantlyinfluence the patient's decision by 66.4%. (3) The process variable partiallyhas a significant influence on the patient's decision by 0%. While theresults of the simultaneous testing of the F test can be concluded that thevariables of people, physical evidence, and processes have a significanteffect on the patient& decision to give birth at Rajawali Citra Hospital. Thecoefficient of determination RÂ² is obtained by 15.2%, patient decisions areinfluenced by the three independent variables, namely people, physicalevidence, and process. While the remaining 84.8% is influenced byunknown variables.Keywords : Physical Evidence; Patient Decision; Person; Process;Rajawali Citra Hospital